Structural, optical and conductivity study of hydrothermally synthesized TiO2 nanorods. (20th January 2020) - Kumar, N Santhosh; Kumar, S K Naveen; Yesappa, L
Abstract: TiO2 nanorods are synthesized by hydrothermal method using the commercially available TiO2 nanopowder (P25) as a precursor. This work mainly focused on the study of the various properties and comparison among the P25, 20 mg TiO2 nanorods and 40 mg TiO2 nanorods by different characterizations. Fourier Transform Infrared Spectroscopy (FTIR) was carried out and the results confirmed the formation and presence of TiO2 nanorods by shifting peak positions from 1433 cm −1 to 1424cm −1 and 1420cm −1 . The x-ray diffraction (XRD) results indicate that the crystallinity of TiO2 nanorods increased significantly and was confirmed by the variation in the diffraction peak intensity and the peak at 2 θ  = 25.23° is conformed the anatase phase. The Field Emission Scanning Electron Microscope (FESEM) images clearly show the formation and presence of TiO2 nanorods. Thermogravimetric Analysis (TGA) and Differential Thermal Analysis (DTA) reveal that increasing in thermal stability and differential scanning calorimeter (DSC) evaluates the increase in melting temperature of TiO2 nanorods. The UV–vis absorption spectra show the absorption peak redshift towards higher wavelength and it leads to expansion of optical activities of TiO2 nanorods. The optical band gap energy was found to be decreased to 5.3, 5.2 and 4.9 eV for P25, 20 and 40 mg respectively. The dielectric constant has increased twice and the dielectric loss by almost ten times compared to dielectric constant and dielectric loss of the P25. The current versus voltage (I-V) characteristics show the linear curve which reveals the easy flow of current is more in TiO2 nanorods. From the obtained results, it could be concluded that TiO2 nanorods are suitable for potential applications.